Applying Computational Methods to Interpret Experimental Results in Tribology and Enantioselective Catalysis - (:unkn) unknown (My University, 2013)
Computational methods are rapidly becoming a mainstay in the field of chemistry. Advances in computational methods (both theory and implementation), increasing availability of computational resources and the advancement of parallel computing are some of the major forces driving this trend. It is now possible to perform density functional theory (DFT) calculations with chemical accuracy for model systems that can be interrogated experimentally. This allows computational methods to supplement or complement experimental methods. There are even cases where DFT calculations can give insight into processes and interactions that cannot be interrogated directly by current experimental methods. This work presents several examples of the application of computational methods to the interpretation and analysis of experimentally obtained results. First, triobological systems were investigated primarily with full-potential linearized augmented plane wave (FLAPW) method DFT calculations. Second, small organic molecules adsorbed on Pd(111) were studied using projector-augmented wave (PAW) method DFT calculations and scanning tunneling microscopy (STM) image simulations to investigate molecular interactions involved in enantioselective heterogeneous catalysis. A method for method for calculating pressure-dependent shear properties of model boundary-layer lubricants is demonstrated. The calculated values are compared with experimentally obtained results. For the case of methyl pyruvate adsorbed on Pd(111), DFT-calculated adsorption energies and structures are used along with STM simulations to identify species observed by STM imaging. A previously unobserved enol species is discovered to be present along with the expected keto species. The information about methyl pyruvate species on Pd(111) is combined with previously published studies of S-α-(1-naphthyl)-ethylamine (NEA) to understand the nature of their interaction upon coadsorption on Pd(111). DFT calculated structures and energies are used to identify potential docking complexes and STM simulations are compared to the experimental STM images.
Keywords: Computational Chemistry; Density Functional Theory; Enantioselective Catalysis; STM; Surface Chemistry; Tribology